Vitalidade no centro antigo Teresina, Piauí Praça Marechal Deodoro: uma intervenção contemporânea em área de valor patrimonial - Rocha, Nádja Marcella Soares da (2012)
This study deals with the discussions of contemporary interventions in public spaces in areas of heritage value. The product of this dissertation is an Intervention Project to Marechal Deodoro Square located in Teresina/PI center. The starting point for understanding the theme of this study is to investigate the accessibility and vitality of a public space - through relationship between form and uses. The spatial properties of accessibility and visibility as well as the distribution of land use - factors were associated with distinct patterns of vitality - and compared to usage patterns observed in situ and statements from users obtained through the results of the questionnaires. In attention to questions about the building constructed, particularly in historical centers, considers the guidelines to define intervention strategies in the square, consisted in the development of simulations that after evaluation of results of redesign, was chosen the best option to meet the necessary requirements to the performance, considering the spatial properties of integration and visibility that meet these requirements. Therefore, the "Intervention Project" carried out for the Marechal Deodoro Square characterization proposed items are discussed: spatial structure, vegetation, road network, pavements, street furniture and lighting